Investigating the Mechanism of Strong Roof Weighting and Support Resistance Near Main Withdrawal Roadway in Large-Height Mining Face - Junwu Du; Qingxiang Huang (Lithosphere, 2024)
Aiming at investigating the strong roof weighting when the large height mining face is nearing the main withdrawal roadway, the 52,304 working face (WF) nearly through the main withdrawal roadway mining in a colliery of Shendong coalfield was taken as the research background. The ground pressure, roof structure, and superposition effect of stress in the last mining stage were studied by field measurement, physical simulation, and numerical calculations. The obtained results demonstrated that the main roof formed the “long step voussoir beam” structure under the influence of the main withdrawal roadway. The superposition effect of the front abutment pressure of the WF and the concentrated stress of the main withdrawal roadway caused the stress asymmetrical distribution on the two sides -level hard rock straof the main withdrawal roadway, and the stability of the pillar on the mining side decreases. The initial average periodic weighting interval was 20.7 m. While the WF approaches the main withdrawal roadway, the pillar near the WF of the main withdrawal roadway collapsed, the main roof was broken ahead of the WF, and the actual roof control distance of support and the periodic weighting interval increased by 2.56 and 1.26 times the normal state, respectively. Consequently, the “static load” of the immediate roof and the “dynamic load” of the sliding unsteadiness of the long step voussoir beam increased. The structural model of the “long step voussoir beam” under the superposition of “static and dynamic load” was established concerning those results, and an expression was proposed to compute the support resistance. Meanwhile, the mechanism of strong roof weighting was revealed when the WF was nearly through the main withdrawal roadway. The research conclusion is expected to provide a guideline for the safe withdrawal of the large-height mining faces under similar conditions.